Targeted Interdisciplinary Model for Evaluation and Treatment of Neuropsychiatric Symptoms (TIME) in home care services: a cluster randomized feasibility trial - Kari-Anne Hoel; Bjørn Lichtwarck; Anette Væringstad; Ingvild Hjorth Feiring; Anne Marie Mork Rokstad; Geir Selbæk; Jūratė Šaltytė Benth; Sverre Bergh (BMC, 2022)
Abstract Background Behavioral and psychological symptoms of dementia (BPSD) occur frequently in people with dementia and can contribute to an increased need for help and a reduced quality of life, but also predict early institutionalization. The Targeted Interdisciplinary Model for Evaluation and Treatment of Neuropsychiatric Symptoms (TIME) might be a useful personalized approach to BPSD in people with dementia. The main objective of this feasibility trial was to explore the trial design and methods along with the patients' and the home care staff's acceptance of the TIME intervention before developing a definitive trial. Additionally, we wanted to explore whether TIME could be appropriate for staff in home care services in their approach towards people with dementia with anxiety and depression. Methods This was a 18-month feasibility trial using a parallel cluster randomized controlled design. Nine municipalities from the eastern part of Norway (clusters) - 40 people with dementia and 37 of their next of kin- were randomized to the TIME intervention or to treatment as usual. In addition, qualitative data as field notes were collected and summarized. Results The staff in home care services experienced TIME as an appropriate method; in particular, the systematic approach to the patient's BPSD was experienced as useful. However, the completion of the assessment phase was considered exhaustive and time-consuming, and some of the staff found it challenging to find time for the case conferences. Conclusions We consider that TIME, with some adjustments, could be useful for staff in home care services in cases where they face challenges in providing care and support to people with dementia. This feasibility trial indicates that we can move forward with a future definitive randomized controlled trial (RCT) to test the effect of TIME in people with dementia receiving home care services. Trial registration ClinicalTrial.gov identifier: SI0303150608.